Reflections on Learning and Student Well-being and Learning Achievement - Barokah Widuroyekti; Hadiqotul Luluk; Arifin Nur Budiono; Yurike Kinanthy Karamoy; Lindsay N. Bergsma (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to measure the impact of learning reflection activities on student well-being and learning achievement. The independent curriculum is a transformative curriculum from the previous curriculum. One of the goals of the independent curriculum is to create prosperous students (student well-being). The well-being of students will have an impact on high academic achievement. One effort to realize these two things is by carrying out learning reflection activities. Method: The subjects of this research were students in phase B, namely class IV students at Gambirono State Elementary School 03. This research is quantitative and experimental, with a pretest-posttest control group design. The data collection method was a student well-being questionnaire and a test on Indonesian language subjects. The learning reflection used is the 4F model. The data analysis technique uses the t-test. Results: The research results show that learning reflection using the 4F model impacts student well-being and learning achievement in Indonesian language subjects. Novelty: This research can be used as a reference for schools and teachers in creating a comfortable atmosphere, input about the pattern of student learning outcomes with their level of school well-being, support the importance of comfort to support student learning outcomes, and be used as a reference and consideration for similar research.